Poetry as flowering of life forms: Rancière's reading of Emerson. Issue 4 (6th June 2016) - Arsić, Branka
Abstract : The essay discusses the shift in Rancière's theory concerning the aesthetic regime discussed in Aisthesis . Whereas in previous work Rancière treated the novel as the genre that best embodies his understanding of the modern, in Aisthesis poetry assumes such a role, and is afforded the power to express its historical situation. For him the poetics formulated by Emerson announces the arrival of the modern aesthetic regime while simultaneously distancing itself from the poetic programme of the romantics. My essay reconstructs Rancière's reading of modern poetics while investigating its consequences for our understanding of American Transcendentalism in general and Emerson in particular.